2023
DOI: 10.1088/1361-6668/ace662
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microstructure and superconducting properties of MgB2 bulk samples with Mg addition and Mg/hBN co-additions

Abstract: The microstructure of polycrystalline MgB2 has a strong influence on the current carrying ability, with grain boundaries and non-superconducting nanoparticles acting as good flux pinning centres which improve the local (intrinsic) critical current density (Jc) of the material, whereas porosity and poor connectivity between grains or particles adversely affect macroscopic current transport. Previous studies have found that hBN doping improves intrinsic Jc by introducing nanoscale flux pinning centres, and Mg do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…As mentioned in Introduction, for more than 20 years, since the discovery of the superconductivity in MgB 2 , scientists have been exploring the possibility of increasing the pinning and, hence, the critical current density using various additives [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ,…”
Section: Effect Of Additions On Structure and Superconductive Charact...mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned in Introduction, for more than 20 years, since the discovery of the superconductivity in MgB 2 , scientists have been exploring the possibility of increasing the pinning and, hence, the critical current density using various additives [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ,…”
Section: Effect Of Additions On Structure and Superconductive Charact...mentioning
confidence: 99%
“… ( a )—The schemes of an SFCL model and a testing circuit for the simulation of a fault event. ( b )—Typical oscilloscope traces of the current in a protected circuit (black, solid curve) and the voltage drop across the primary coil of the SFCL model (red, dashed curve) at 50 Hz and about 4 K (from [ 90 ]). The experiment details are described in [ 120 ].…”
Section: Figurementioning
confidence: 99%
“…However, PIT MgB 2 wires have several disadvantages, such as a large number of voids, poor connections between grains, low density of pinning centers, low irreversible magnetic field, and large grains [ 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Current research has shown that doping allows for increasing the density of pinning centers [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%